KARAKTERISTIK PEMBURU LEBAH MADU DI KOMPLEKS HUTAN MEKONGGA - Rosmarlinasiah Rosmarlinasiah (Universitas Haluoleo, 2016)
The existence of various types of forest vegetation in the potency for beeforage on nectar and pollen form which then contributes to the economy of forest communities through the results of honey and other bee products. The ability of people to use the results in an optimal and sustainable bee closely related to the characteristics of the community. The determine the characteristics of the forest hunter bees (Apis dorsata Binghamii), has conducted research on community forest around of Complex Mekongga Forest namely in the village Ulunggolaka, sub district Latambaga Kolaka, Talodo village sub-district Lalolae Kolaka Eastern, province of Southeast Sulawesi. Methods used were interviews with respondents selected by purposive sampling. The results showed that the age of respondents less than 60 years old and classifieds as productive, not completed primary school education up to the end of primary school as much as 61.05%, and did not finish junior high school to high school completed in only 38.95%. Tribes are indigenous Mekongga dominate as much as 62.10% and comers from Bugis Maros much as 37.89%. Ownership of land is land owned by the most narrow land (0.1 hectares to 1.66 hectares) as much as 84.21%. Experience hunting bees lived more than 10 years (87,37%), the division of tasks in hunting bees consists of tree-climbing 43%, and towing rope from under the tree 57%. Keywords: Characteristics of society, hunters bee, Apis dorsata Binghamii, Mekongga forest.